2007
DOI: 10.5194/gh-62-159-2007
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphosite assessment in Montesinho Natural Park (Portugal)

Abstract: Abstract. The Montesinho Natural Park (MNP), with an area of about 750 km2, is one of the largest protected areas in Portugal. Since its inauguration as a natural park in 1979, geological and geomorphological aspects have not been taken into consideration in its nature conservation policies. Over the last few years, this deficit has been compensated with an assessment of its geomorphological heritage. The assessment was made possible due to a research project on the geological heritage of the natural parks of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
235
0
33

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(269 citation statements)
references
References 2 publications
1
235
0
33
Order By: Relevance
“…They divide the methods into two groups: qualitative and quantitative, but do not indicate the best ones (Pereira et al 2007, Reynard et al 2007, Rybár 2010, Baca and Schuster 2011, Bruschi et al 2011, Fassoulas et al 2012. They do, however, define the criteria, which should be taken into account in the assessment of geosites.…”
Section: Assessment Of Urban Geosites -Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…They divide the methods into two groups: qualitative and quantitative, but do not indicate the best ones (Pereira et al 2007, Reynard et al 2007, Rybár 2010, Baca and Schuster 2011, Bruschi et al 2011, Fassoulas et al 2012. They do, however, define the criteria, which should be taken into account in the assessment of geosites.…”
Section: Assessment Of Urban Geosites -Results and Discussionmentioning
confidence: 99%
“…kubaliková (2013) has identified the following groups of criteria for assessing geosites: 1 -the scientific and intrinsic values (integrity, rarity; scientific knowledge; morphology, genesis), 2 -the exemplarity and pedagogical potential (exemplarity, clarity; educational facilities; use for education), 3 -accessibility and visibility of the site and the presence of tourist infrastructure (tourist services; local products; accessibility), 4 -the existing threats and risks, assessing conservation activities or the existing legislative protection of the site (conservation activities; risks and threats; current status), and 5 -added values (cultural values; ecological value; aesthetic/landscape value). The author made a quantitative assessment of seven methods presented by Bruschi and Cendrero (2005), Coratza and Giusti (2005), Pralong (2005), Serrano and Gonzales-Trueba (2005), Pereira et al (2007), Reynard et al (2007) and Zouros (2007), and concluded that the less relevant methods for assessing geosites and geomorphosites for geotourism purposes are those described by Coratza and Giusti (2005) and Reynard et al (2007), which use less than half the geosite evaluation criteria outlined by this author. In turn, kubaliková (2013) described the methods by Pralong (2005) and Pereira et al (2007) as those best exploiting these assessment criteria.…”
Section: Assessment Of Urban Geosites -Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A detailed review of quantitative methods evaluating different values of abiotic objects in order to assess their usefulness for the development of geotourism has been recently published by Kubalíkova (2013). She described the methods used in Italy (Panizza 2001, Coratza andGiusti 2005), Spain (Serrano andGonzalez-trueba 2005, Bruschi andCendrero 2005), Portugal (Pereira et al 2007, Pereira andPereira 2010), Greece (Zouros 2005(Zouros , 2007, and Switzerland (Pralong 2005, Reynard et al 2007. Based on the analysis of the criteria and categories used in the mentioned quantitative methods, Kubalikova (2013) proposed her own method of geosite evaluation for geotourism purposes.…”
Section: Introductionmentioning
confidence: 99%